Etika dan Hukum Perceraian serta Poligami bagi Pegawai Negeri Sipil - Adi Riyanto (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2019)
The purpose of this study is to find out what regulations are applied among Civil Servants (PNS) regarding Divorce and to find out the causes of Divorce among Civil Servants (PNS). The research method used is normative juridical, which is an approach method by studying the law which is conceptualized as a norm or rule that applies in society, and serves as a reference for everyone's behavior. data collection tool through library research. ata used secondary, that is data obtained through the study of documentation by reading scientific books, magazines, internet, newspapers and other readings related to research. The results of the study are Regulations on divorce and polygamy regulated in Law Number 1 of 1974 concerning Marriage; Government Regulation Number 45 of 1990 concerning Amendment to Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants; Government Regulation Number 53 of 2010 concerning Discipline Regulation of Civil Servants. Factors that influence divorce are Education, Age of Marriage, Income, Economic Issues, Domestic Violence, Infidelity, Interference of Large Families (Parents).Keywords: ethics; law; divorce; pologamy; government employees AbstrakTujuan penelitian ini adalah untuk mengetahui peraturan-peraturan apa saja yang diterapkan dikalangan Pegawai Negeri Sipil (PNS) mengenai Perceraian dan untuk mengetahui penyebab terjadinya Perceraian dikalangan Pegawai Negeri Sipil (PNS). Metode penelitian yang digunakan adalah yuridis normatif, yaitu metode pendekatan dengan mengkaji hukum yang dikonsepkan sebagai norma atau kaidah yang berlaku dalam masyarakat, dan menjadi acuan perilaku setiap orang. alat pengumpul data melalui studi kepustakaan. ata yang digunakan sekunder, yaitu data yang diperoleh melalui studi dokumentasi dengan cara membaca buku-buku ilmiah, majalah, internet, surat kabar dan bacaan-bacaan lain yang berhubungan dengan penelitian. Hasil penelitian yaitu  Pengaturan mengenai perceraian dan poligami diatur dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan; Peraturan Pemerintah Nomor 45 Tahun 1990 tentang Perubahan Atas Peraturan Pemerintah Nomor 10 Tahun 1983 tentang Izin Perkawinan dan Perceraian bagi Pegawai Negeri Sipil; Peraturan Pemerintah Nomor 53 Tahun 2010 tentang Peraturan Disiplin Pegawai Negeri Sipil. Faktor-faktor yang mempengaruhi perceraian adalah Pendidikan,  Lama Usia Perkawinan, Pendapatan , Masalah Ekonomi ,Kekerasan Dalam Rumah Tangga, Perselingkuhan, Campur Tangan Keluarga Besar (Orang Tua).Kata Kunci : etika; hukum; perceraian; pologami; pegawai negeri sipil